Prodistik; madrasah management to develop IT skill in industrial revolution 4.0 era - Kusumaningrum, Anita; Rozi, Fathor; Wahyuni, Eka (ATTARBIYAH: Journal of Islamic Culture and Education, 2022)
In the era of the industrial revolution 4.0, which requires the younger generation to develop expertise in the IT field, educational institutions must also develop Madrasah management to provide this knowledge and skills for their students. This study aims to examine Prodistik as Madrasa management in developing IT skills in the era of the industrial revolution 4.0 so that Madrasah graduates can also master technology. The approach used in this research is descriptive qualitative with case study type. At the same time, the research location is in MA Negeri 2 Probolinggo. Data collection techniques used include observation and in-depth interviews equipped with documentation. The data analysis technique refers to the Miles andHuberman technique, which allows data reduction, data display, and data verification/conclusion. The study results indicate that Madrasah management in implementing Prodistik is collaborating with ITS Surabaya, forming an IT Skills Vocational Team and ToT, developing the Prodistik curriculum, and monitoring and evaluating programs in collaboration with ITS every semester. The conclusion is the increasing ability of MA Negeri 2 Probolinggo students in the IT field who are able to make various useful products by utilizing IT in the preparation of Final Projects and achievements in various IT competitions The implication is that educational institutions can realize Madrasah programs to the maximum if there is cooperation with other relevant institutions or institutions.